1988
DOI: 10.1126/science.3041594
|View full text |Cite
|
Sign up to set email alerts
|

Wound Macrophages Express TGF-α and Other Growth Factors in Vivo: Analysis by mRNA Phenotyping

Abstract: The presence of macrophages is required for the regeneration of many cell types during wound healing. Macrophages have been reported to express a wide range of mitogenic factors and cytokines, but none of these factors has been shown in vivo to sustain all the wound-healing processes. It has been suggested that transforming growth factor-alpha (TGF-alpha) may mediate angiogenesis, epidermal regrowth, and formation of granulation tissue in vivo. Macrophages isolated from a wound site, and not exposed to cell cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
408
1
11

Year Published

1989
1989
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,043 publications
(426 citation statements)
references
References 42 publications
6
408
1
11
Order By: Relevance
“…The PCR reaction was performed as described. 9,14,15 As a control reaction of PCR, ␤-actin was also used in each run. Briefly, 250 ng of the RNA was used for RT-PCR.…”
Section: Detection Of Apoptotic Cells By End Labeling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR reaction was performed as described. 9,14,15 As a control reaction of PCR, ␤-actin was also used in each run. Briefly, 250 ng of the RNA was used for RT-PCR.…”
Section: Detection Of Apoptotic Cells By End Labeling Methodsmentioning
confidence: 99%
“…6 Hematopoietic cells as well as stromal cells have been reported to express a wide range of substances which may play complex regulatory roles in hematopoiesis. [7][8][9] We have reported previously that the number of macrophage lineage cells significantly increased in the bone marrow of MDS patients as compared with that of the control or de novo AML bone marrow. 10 Furthermore, bone marrow macrophages express tumor necrosis factor (TNF)␣ and interferon (IFN)-␥ which have an accelerating effect on apoptosis.…”
Section: Introductionmentioning
confidence: 98%
“…The PCR reaction was performed as described elsewhere. 21,23,24 As a control reaction of PCR, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (196 bp) was also detected in each run. Briefly, 50 ng of the RNA was used for RT-PCR.…”
Section: Patientsmentioning
confidence: 99%
“…18 Hematopoietic cells as well as stromal cells have been reported to express a wide range of substances which may play complex regulatory roles in hematopoiesis. [19][20][21] We have reported previously that the number of macrophage-lineage cells significantly increased in the bone marrow of MDS patients as compared with that of the control or de novo AML bone marrow. 22 Therefore not only the proliferation of MDS clone cells but also the abnormal function of stromal cells of the bone marrow may be involved in mechanisms causing cytopenias in MDS through disturbed regulation of the expression and production of growth factors and cytokines.…”
Section: Introductionmentioning
confidence: 98%
“…It is likely that macrophages play an important role in tendon healing since these cells function to scavenge cellular debris following injury and they can release growth factors that induce extracellular matrix synthesis [13] and stimulate fibroblasts or other stem cells to proliferate [5]. Previous studies of wound healing in other tissues clearly indicate that macrophage accumulation is an early event in the healing process [21]. For example, Wright et al recently reported that macrophage-lineage cells accumulate in a healing medial collateral ligament injury in a mouse model [28].…”
Section: Introductionmentioning
confidence: 99%